Pengaruh Ukuran Perusahaan, Profitabilitas, Likuiditas, Solvabilitas, Dan Pertumbuhan Perusahaan Terhadap Opini Audit Going Concern ( Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Bei) Tahun 2011-2014) - Saifudin, Aris; , Dra. Rina Trisnawati, M.Si, Ak, Ph.d (2016)
This study aimed to describe empirically the effect of firm size, profitability, liquidity, solvency, and growth of the company going concern audit opinion on manufacturing companies listed in Indonesia Stock Exchange in 2011-2014. The population in this study using manufacturing companies listed in Indonesia Stock Exchange in 2011-2014. Sampling was done by using a purposive sampling method and obtained a sample of 56 companies. Secondary data collection methods based on data published BEI during the period 2011-2014. Data were analyzed using logistic regression. The results showed that company size, profitability, and growth of the Vendor does not have a significant impact on the going concern audit opinion. While liquidity significantly and negatively related to the going concern audit opinion, and solvency positive and significant impact on the going concern audit opinion.